Positive expiratory pressure breathing speeds recovery of postexercise dyspnea in chronic obstructive pulmonary disease. (24th September 2018) - Ubolsakka‐Jones, Chulee; Pongpanit, Khajonsak; Boonsawat, Watchara; Jones, David A.
Abstract: Objectives: Faster recovery of postexertional dyspnea might enable chronic obstructive pulmonary disease (COPD) patients to undertake more physical activity. The purpose of this study was to determine whether breathing with a positive expiratory load to reduce dynamic hyperinflation (DH) would hasten recovery. Methods: Thirteen male COPD patients (59 ± 7 years; Global Initiative for Obstructive Lung Disease Stages II and III) took part in a randomized cross‐over trial in which they exercised by self‐paced spot marching. Interventions at the end of exercise consisted of six breaths against either a 5‐cm H2 O expiratory load (positive expiratory pressure [PEP]) or no load (Sham), with 3‐hr rest between interventions. Recovery was followed for the next 10 min. Primary outcome measures were dyspnea during recovery and inspiratory capacity (IC), measured at rest, at the end of exercise and after the intervention; oxygen saturation, end‐tidal CO2, heart rate, and breathing frequency were also monitored. Results: Patients exercised for 5 min reaching a heart rate of 70% age‐predicted maximum and developed dyspnea of 3–4 on the Modified Borg CR10 scale. Dyspnea recovered significantly faster after the PEP intervention in all patients, taking 2.8 ± 0.4 min to return to baseline compared with 5.1 ± 0.6 min for Sham ( p < 0.01). IC declined at the end of exercise and was improved by PEP (+270 220–460 ml, median, interquartile range) more than Sham (+100, 40–160 ml). However, PEP was equally effective in reducing dyspnea in all patients irrespective of the degree of DH. Changes in oxygen saturation, end‐tidal CO2, heart rate, and breathing frequency were similar in PEP and Sham. Conclusions: Positive expiratory pressure breathing is an effective means of reducing postexercise dyspnea and DH in COPD. The benefits were not limited to patients with high DH suggesting PEP may be used to speed recovery and increase the volume of exercise during pulmonary rehabilitation sessions and physical activity at home or work.